Examining resilience in Singapore in the face of COVID-19 community restrictions - Chan, Alyssa Yenyi; Tan, Chuen Seng; Chan, Felicia Jia Hui; Soh, Alexius Matthias Sheng En; Chen, Mark I-Cheng; Hildon, Zoe Jane-Lara (Frontiers in Psychology, 2023)
To curb transmission of COVID-19, Singapore has experienced multiple, ongoing community restrictions. Gaining the ability to adapt and thrive under pressure will be key to addressing effects of these restrictions on mental health. To inform this, we examine the following research questions, (1) What typifies adversity related to living with on-off COVID-19 restrictions? (2) Who are the resilient? (3) How are negative effects of adversity attenuated? Participants were a part of the Strengthening Our Community's Resilience Against Threats from Emerging Infections (SOCRATES) cohort, invited to participate in this survey either via email or text message. Using the community survey data (N=1364), analyses such as Wilcoxon rank sum test and logistic regression were conducted. Adversities are identified as circumstances associated with a significant increase in Hospital Anxiety and Depression Scale (HADS) scores. It is typified by having financial worries; experiencing heightened emotions and frequent crying; having "out of body" experiences; having to move frequently or not being able to settle into accommodation; and regularly feeling mistreated by someone close to you. Being resilient in the face of adversity was determined by HADS scores for depression and anxiety (dichotomized at the median) and characterized by overall better social relationships such as having harmonious living situations and solution-driven coping strategies, especially the ability to harness the belief that difficult situations can lead to growth. In accordance with the Loads-Levers-Lifts model, results indicate that initiatives that increase access to identified protection, while minimizing exposure to known adversities where possible, will promote resilience under COVID-19 restrictions.